(untitled) - Phạm, Huy Kỳ (Thành phố Hồ Chí Minh, 2006)
Sách giới thiệu các vật dụng, vật liệu cần thiết và cách chế biến món Sushi và Sashimi
Keywords: Cookery, Japanese,Cookery (Fish ),Sushi,Sashimi